Two Modes of Transgenerational Information Transmission - Shea, N (MIT Press, 2013)
The explosion of scientific results about epigenetic and other parental effects appears bewilderingly diverse. An important distinction helps to bring order to the data. Firstly, parents can detect adaptively-relevant information and transmit it to their offspring who rely on it to set a plastic phenotype adaptively. Secondly, adaptively-relevant information may be generated by a process of selection on a reliably transmitted parental effect. The distinction is particularly valuable in revealing two quite different ways in which human cultural transmission may operate.